2010
DOI: 10.1177/1479972310376082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel sputum clearance technique—hydro-acoustic therapy (HAT) in adult patients with cystic fibrosis: A feasibility study

Abstract: This study was designed to investigate the efficacy, safety and patients' acceptance of a novel system for sputum clearance--Hydro Acoustic Therapy (HAT) in patients with cystic fibrosis (CF). This is a prospective crossover study where 18 patients received 6 sessions of physiotherapy over 6 separate days. These consisted of 2 sessions of either HAT, flutter valve or and sitting in the bath with sounds without vibration (placebo) for 30 minutes each. The efficacy was investigated by measuring the weight of wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Pfleger et al (1992) found significant improvements in FEV 1 after autogenic drainage and high-pressure PEP-mask (n=14, Cohen's d z 0.09 and 0.22) [9]. Jarad, Powell and Smith (2010) reported a statistically significant reduction in FEV1 following hydro-acoustic therapy (n=19, Cohen's dz=0.12) or flutter (n=19, Cohen's dz=0.06) [10]. Nevertheless, these changes returned to baseline on the second study day [10].…”
Section: Forced Expiratory Volume In the First Secondmentioning
confidence: 97%
See 2 more Smart Citations
“…Pfleger et al (1992) found significant improvements in FEV 1 after autogenic drainage and high-pressure PEP-mask (n=14, Cohen's d z 0.09 and 0.22) [9]. Jarad, Powell and Smith (2010) reported a statistically significant reduction in FEV1 following hydro-acoustic therapy (n=19, Cohen's dz=0.12) or flutter (n=19, Cohen's dz=0.06) [10]. Nevertheless, these changes returned to baseline on the second study day [10].…”
Section: Forced Expiratory Volume In the First Secondmentioning
confidence: 97%
“…Jarad, Powell and Smith (2010) reported a statistically significant reduction in FEV1 following hydro-acoustic therapy (n=19, Cohen's dz=0.12) or flutter (n=19, Cohen's dz=0.06) [10]. Nevertheless, these changes returned to baseline on the second study day [10].…”
Section: Forced Expiratory Volume In the First Secondmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have validated sputum production as a reproducible outcome measure in CF and reported sputum production to be similar within a week interval 27 and on a day-to-day basis during disease stability. 28 In this study, sputum production was relatively similar in each pair when the techniques were compared.…”
Section: Discussionmentioning
confidence: 72%
“…29 Although dry weight of sputum has been considered as more accurate in reflecting sputum quantity, contradictory findings exist in the literature regarding the correlation between wet and dry weight. While some studies found no difference in the ratio of dry to wet sputum weight, 21 and no significant difference in wet or dry sputum weight between treatment groups and placebo, 28 other studies have found a significant difference between treatments when considering both wet and dry weight. 30 Although a standardised protocol was used in this study, the lack of sufficient recoding of total coughs in the interventions, as spontaneous coughs can influence sputum production, may have affected sputum weight.…”
Section: Discussionmentioning
confidence: 95%